La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Linear assembly of hexadecanethiol coated gold nanoparticles - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2008)
An interesting formation of linear assembly of hexadecanethiol coated gold nanoparticles is demonstrated. The nanoparticles used were synthesized in an organic medium and then were subjected to digestive ripening to finally yield monodisperse nanoparticles. A simple drop casting on TEM grid lead to the results observed. Based on the thermo gravimetric analysis, it is hypothesized that inclusion of the particles in Au(I)-thiolate template is mainly responsible for the formation of linear assembly. (c) 2008 Elsevier B.V. All rights reserved.

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic

Large reduction in the magnitude and thermal variation of Frank elastic constants in a gold nanorod/nematic composite - Madhuri, P. Lakshmi; Prasad, S. Krishna; Shinde, Pravin; Bhagavatula L. V. Prasad (Journal of Physics D: Applied Physics, 2016)
We report measurements of splay and bend Frank elastic constants in a composite comprising a nematic liquid crystal doped with a small concentration of sterically stabilized gold nanorods. The composite exhibits not only a large reduction in the magnitude of the threshold voltage for switching (Vth, 20%), as well as of the splay (K11, 40%) and bend (K33, 40%) elastic constants, but also presents an unprecedented feature: a substantial diminution in the temperature dependence of these parameters, almost to the point of becoming thermally invariant. This observation is significant because the electro-optic switching of liquid-crystal devices is largely controlled by the K11 and K33 elastic constants. Electrical conductivity measurements also show interesting behavior upon the inclusion of nanorods. Whereas the intrinsic Arrhenius behavior governing the temperature dependence is enhanced, the frequency dependence shows qualitative features of Jonscher’s universal model, albeit with a higher exponent. Further, photoisomerization of an azobenzene guest component provides an additional influence on the elastic constants. The results are discussed in terms of (a) the effect of the order parameter dependence seen from the viewpoint of an extended mean-field model,and (b) local order. The advantage of incorporating nanorods with photofunctionality is also pointed out.